MAKNA OTONOMI DAERAH DI WILAYAH LAUT BAGI MASYARAKAT PESISIR KOTA SEMARANG - Kushandajani, Kushandajani (Jurnal Media Hukum, 2010)
The main problem in this study was how the social significance of the existence of local autonomy regulation through the Law No. 32 of 2004. The specific questions tried to be answered in this study were whether the Law could preserve the social values rooted from the local culture, could increase the participation of the society, and finally could prosper the local society.Law No. 32 of 2004 contains local authority in the sea area which includes two categories, â€œto receive profit shareâ€ and â€œto have the authority to manage the resources in sea areaâ€ as far as 4 miles from coast line for the regions which own the sea. Through the delegation of authority in managing the coastal area, it was expected that the regional governance would develop the coastal society to be more prosper.The local government and the coastal society didnâ€™t realize and couldnâ€™t give an appropriate response to the change design in Law. The application of local autonomy which regulated territorial power division hadnâ€™t yet been meaningful for the coastal society in Semarang City. Society development programs could not increase the participation yet. Meanwhile, economic development hadnâ€™t yet been able to increase the costal societyâ€™s prosperity.Keywords: Local autonomy, the coastal society, prosperity.